(untitled) (Comprehensive Journal of Science, 2025)
Criminal mediation is an innovative and important alternative to traditional custodial sentences and represents a potential turning point in the Libyan legal system. Currently, Libyan law does not explicitly adopt this system, but the need for it is growing with increasing pressure on the judicial system and awareness of the need to seek more effective and humane solutions to crimes. The application of criminal mediation opens the door to restorative justice, which focuses on repairing the harm done to the victim and rehabilitating the offender, rather than solely on punishment. Through this approach, the victim can quickly receive compensation or an apology, giving them a sense of satisfaction and empowerment. In turn, the offender understands the true impact of their crime and takes responsibility for their actions, helping them avoid recidivism.However, the path to adopting this system is not easy, as it faces challenges such as the absence of an appropriate legislative framework, the need to change judicial culture, and the availability of qualified personnel to implement this process.Adopting criminal mediation could represent an important step toward developing the Libyan criminal justice system, making it more capable of achieving comprehensive justice that goes beyond punishing perpetrators, but also seeks to reform and reintegrate them into society.